Leadership roles of principals in international secondary schools: evidence from Malaysia - Lam, Chee Fong (2025)
The number of international schools globally has been growing exponentially in the last few decades. Malaysia has a similar growth rate of international schools during these two decades. As more international schools are established, more principals are required to lead the schools. This study focuses on the role of principals in leading international secondary schools in Malaysia.